An archaeological excavation of a medieval fishermen's midden at Castle Hill Pumping Station, Banff. Issue 1 (March 2015) - Bailey, Laura; Holden, Tim; Franklin, Julie; Smith, Catherine; Cerón-Carrasco, Ruby
Abstract : An archaeological excavation in the footprint of a proposed pumping station at the foot of the seaward slope of Castle Hill, Banff, revealed the remains of a late medieval coastal processing centre. Several features were uncovered including an extensive spread of midden material dating between the 11 th and 13 th centuries, a series of shallow enclosure ditches and a later rectangular building. Contained within the midden were knives, animal and fish bone, marine shells together with medieval pottery and possibly the largest collection of medieval fish hooks recovered in Scotland. The archaeological material provides evidence that the stretch of shoreline along the west bank of the River Deveron was the site of a small fishing settlement during the early development of the burgh of Banff. Results of the excavation make an important contribution to our understanding of late medieval economies in Scotland, particularly in relation to the collection and use of local resources and the development of the commercial fishing industry.